Regulatory myeloid cells paralyze T cells through cell-cell transfer of the metabolite methylglyoxal - Baumann, Tobias; Dunkel, Andreas; Schmid, Christian; Schmitt, Sabine; Hiltensperger, Michael; Lohr, Kerstin; Laketa, Vibor; Donakonda, Sainitin; Ahting, Uwe; Lorenz-Depiereux, Bettina; Heil, Jan Erik; Schredelseker, Johann; et al. (Nature immunology, 2020)
Regulatory myeloid immune cells, such as myeloid-derived suppressor cells (MDSCs), populate inflamed or cancerous tissue and block immune cell effector functions. The lack of mechanistic insight into MDSC suppressive activity and a marker for their identification has hampered attempts to overcome T cell inhibition and unleash anti-cancer immunity. Here, we report that human MDSCs were characterized by strongly reduced metabolism and conferred this compromised metabolic state to CD8(+) T cells, thereby paralyzing their effector functions. We identified accumulation of the dicarbonyl radical methylglyoxal, generated by semicarbazide-sensitive amine oxidase, to cause the metabolic phenotype of MDSCs and MDSC-mediated paralysis of CD8(+) T cells. In a murine cancer model, neutralization of dicarbonyl activity overcame MDSC-mediated T cell suppression and, together with checkpoint inhibition, improved the efficacy of cancer immune therapy. Our results identify the dicarbonyl methylglyoxal as a marker metabolite for MDSCs that mediates T cell paralysis and can serve as a target to improve cancer immune therapy. Myeloid-derived suppressor cells (MDSCs) residing within tumors can impede immune responses. Knolle and colleagues show that MDSCs poison immune cells by producing methylglyoxal, which functionally alters their cellular metabolism and hence their effector responses.